Establishment of rat embryonic stem cells and making of chimera rats. - Shinobu Ueda; Masaki Kawamata; Takumi Teratani; Taku Shimizu; Yoshitaka Tamai; Hiromasa Ogawa; Katsuyuki Hayashi; Hiroyuki Tsuda; Takahiro Ochiya (PLoS ONE, 2008)
The rat is a reference animal model for physiological studies and for the analysis of multigenic human diseases such as hypertension, diabetes, neurological disorders, and cancer. The rats have long been used in extensive chemical carcinogenesis studies. Thus, the rat embryonic stem (rES) cell is an important resource for the study of disease models. Attempts to derive ES cells from various mammals, including the rat, have not succeeded. Here we have established two independent rES cells from Wister rat blastocysts that have undifferentiated characters such as Nanog and Oct3/4 genes expression and they have stage-specific embryonic antigen (SSEA) -1, -3, -4, and TRA-1-81 expression. The cells were successfully cultured in an undifferentiated state and can be possible over 18 passages with maintaining more than 40% of normal karyotype. Their pluripotent potential was confirmed by the differentiation into derivatives of the endoderm, mesoderm, and ectoderm. Most importantly, the rES cells are capable of producing chimera rats. Therefore, we established pluripotent rES cell lines that are widely used to produce genetically modified experimental rats for study of human diseases.